Dynamic extracorporeal life support: A novel management modality in temporary cardio‐circulatory assistance. Issue 4 (29th December 2020) - Lo Coco, Valeria; Swol, Justyna; De Piero, Maria Elena; Massimi, Giulio; Chiarini, Giovanni; Broman, Lars Mikael; Lorusso, Roberto
Abstract: Extracorporeal life support (ECLS) is a temporary mechanical assistance method employed in acute respiratory, cardiocirculatory, and cardio‐respiratory failure, refractory to conventional treatments. Patient's hemodynamic, respiratory and metabolic condition, or situations related to ECLS support or performance, may change during ECLS treatment. Provision of an additional drainage or perfusion cannula, or even of an additional associated device, for example, transaortic suction device or intra‐aortic balloon pump (IABP), may be required to improve the ECLS/patient interaction and effects. Besides such a modified ECLS mode, however, a potential asset is represented by the "dynamic ECLS, " which is the change of the flow direction (drainage or perfusion) in the already implanted cannula during the ECLS run. This particular management may be achieved in venous femoral or jugular cannulation, but it finds an even more appealing potential with the pulmonary artery (PA) cannulation. The PA allows the institution of a multitasking ECLS circuit, ranging from enhanced left ventricle (LV) unloading (drainage from the PA) to a right ventricular support or "central" veno‐venous ECLS (perfusing the PA), tailored according to the patient hemodynamic, gas exchange, metabolic state, underlying cardiac involvement, and ECLS performance. Dynamic ECLS may, therefore, represent an additional option in ECLS management, particularly including the PA cannulation. Based on this new dynamic management of ECLS mode, we propose the Extracorporeal Life Support Organization nomenclature update.